2021
DOI: 10.1177/20533691211005313
|View full text |Cite
|
Sign up to set email alerts
|

Anal and urinary incontinence in nulliparous women – Prevalence and associated risk factors

Abstract: Objective To establish the prevalence and risk factors of urinary and anal incontinence in nulliparous women. Study design Thirty-one catholic convents were sent a validated questionnaire to determine the prevalence and severity of urinary incontinence, and a similarly structured questionnaire to assess anal incontinence. Multivariable regression models were used to determine independent risk factors associated with the likelihood of urinary incontinence or anal incontinence. Main outcome measures Urine/faecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The study found that hormone replacement therapy (HRT), BMI, and age were risk factors for UI in nulliparous women. [30] Additionally, pregnancy itself is a risk factor for UI, [31] and uterine growth pressure [32]and constipation [5] have also been identi ed as risk factors for UI in nulliparous women. The interaction between dietary inorganic salt intake and vaginal deliveries has not been reported in previous articles.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that hormone replacement therapy (HRT), BMI, and age were risk factors for UI in nulliparous women. [30] Additionally, pregnancy itself is a risk factor for UI, [31] and uterine growth pressure [32]and constipation [5] have also been identi ed as risk factors for UI in nulliparous women. The interaction between dietary inorganic salt intake and vaginal deliveries has not been reported in previous articles.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age, especially greater than 70 years, increasing body mass index (BMI), especially greater than 40 kg/m 2 , and a history of any vaginal birth have the greatest associations with UI [3]. The prevalence of UI increases with age even among nulliparous women [9,10]. UI is often part of a geriatric syndrome including falls and cognitive impairment.…”
Section: Risk Factorsmentioning
confidence: 99%